Review: The Reformation of Morals - Shahîd, Irfan (Journal of Semitic studies, 2005)
The Reformation of Morals Yahyā Ibn'Adiyy , translated and introduced by Sidney Griffith (Eastern Christian Texts, Vol. I). Brigham Young University Press, Provo, Utah 2002. xlvi + 137. Price: $34.95 . ISBN: 0-934893-69-1